Development of Ti-Al-Ta-Nb-(Re) near-α high temperature titanium alloy: Microstructure, thermal stability and mechanical properties. (20th May 2022) - Li, Juan; Xu, Yaqun; Xiao, Wenlong; Ma, Chaoli; Huang, Xu
Highlights: The Ta, Nb and/or Re elements were used to increase the microstructural stability of high temperature Ti alloy. The Ta and Nb exhibited weak β-stabilizing ability, while the Re was a strong β-stabilizer and obviously increased the content of β phase. A trace Re addition retarded the growth of ordered α2 precipitates due to the increase of Ta and Nb concentrations in the α phase. Abstract: Mechanical properties and microstructural stability under the service temperature are important to the high temperature titanium alloy. In order to evaluate the potential in increase the service temperature of Ti alloy, two near-α Ti alloys with high content of Al as α-stabilizer and Ta, Nb and/or Re as β-stabilizers were designed and prepared by ingot metallurgy and thermomechanical processing, and the microstructure and mechanical properties before and after thermal exposure at 650 °C for 100 h were characterized. The results indicated that due to the weak β-stabilizing ability of Ta and Nb elements, only a small amount of β phase was formed in Ti-10Al-4Ta-2Nb alloy. With a trace Re addition, the β phase was obviously increased in Ti-10Al-4Ta-2Nb-0.25Re, indicating that the Re was a strong β-stabilizer. Under the same thermomechanical conditions, the Re addition decreased the volume fraction of primary α (αp ) phase and refined the secondary α (αs ) phase evidently. The primary α phase presented an obvious core-shell structure in the Ti-10Al-4Ta-2Nb alloy, with higher Al concentration in the shell. While the core-shell structure was not obvious in the Re-containing alloy due to the Re decreases the diffusion of Al, Ta and Nb elements. A large number of ordered α2 precipitates can be observed in the αp and αs phases of two alloys. The α2 precipitates continuously grew up during thermal exposure, however, their growth rate in the αs phase of Re-containing alloy were lower than that of Ti-10Al-4Ta-2Nb alloy. Although plenty of ordered α2 precipitates formed in the Ti-10Al-4Ta-2Nb alloy, the alloy had a certain plasticity at room temperature. The trace Re addition evidently increased the tensile strength but caused the decrease of the plasticity. After thermal exposure, the strength was further increased, while the plasticity was decreased for both of alloys.